Окружение Сталина - Медведев Рой Александрович (Жизнь замечательных людей, 2010)
Экземпляры: Аб.,3ф.,5ф. (17.09.2012г.) / Инвентарный номер: 47018 / Цена: / Сис.шифр: 66.3(2Рос)6 / Авт.знак: М42 / ББК: 66.3(2Рос)6